Pelaksanaan Program BIPA dan Hasil Pembelajarannya - Kurniawan, Kurniawan; Puspitasari, Devi Ambarwati; Batubara, Didiek Hardadi; Hernina, Hernina; Larasati, Larasati (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
The present study identified the learning outcomes of the program of Indonesian for foreigners (BIPA—Bahasa Indonesia untuk Penutur Asing) and the suitability between student learning outcomes and teaching materials of BIPA. The learning process of BIPA was conducted to improve four language competencies including listening, speaking, reading, and writing. Based on the 2016 and 2017 BIPA teaching reports, thirteen teachers assigned to teach BIPA to Thailand, Vietnam, Myanmar, France, and Russia were successfully able to improve the four language competencies of the students. Meanwhile, the suitability between student learning outcomes and teaching materials of BIPA indicated that: 1) sixty seven BIPA teachers were considered good at adjusting the learning to the teaching materials, 2) four BIPA teachers were rated fair in adjusting the learning to the teaching materials, and 3) ten BIPA teachers were considered poor in adjusting the learning to the teaching materials